Management and funding of the research by the Peruvian National Institute of Health, 2004-2008 - Garro, Gladys; Mormontoy, Henry; Yagui, Martín (Revista peruana de medicina experimental y salud pública, 2010)
The results of the research projects that have been approved and funded by the Instituto Nacional de Salud (Peru) during the period 2004-2008 were analyzed. Out of 182 approved and funded research projects, 150 (82%) were actually performed, 86% (129/150) ended in the final report and only 14% (18/129) were published in indexed journals, the mean time for publication of an article was of 2,7 years. Out of the presented research projects, 68 (45%) were through a competitive fund, 60 (40%) were institutional, 14 (9%) coming from regional (provincial) health directions and 8 (5%) collaborative. The executed budget was of $ 5,032,906.62. The mean amount assigned to each research project was $ 33,552.71 and the cost of each publication was $ 279,605.92; the distribution of the budget according to each study subject was 61% for communicable diseases, 12% for non-communicable diseases and 27% for technological development. The research promotion, development and financing in the Instituto Nacional de Salud during this period have had a decreasing trend, influenced by institutional policy. In order to overcome this situation, not only at an institutional but also at a national level, it is necessary that the State defines its national research policy, respecting the national and regional priorities in health research.